Uses and Limits of Conventional Corporate Governance Instruments : Analysis and Guidance for Reform - Part One - Wong, Simon C.Y. (World Bank, Washington, DC, 2012)
This private sector opinion seeks to demonstrate that while conventional governance mechanisms can be highly effective in many situations, they are not appropriate remedies in all contexts. In some cases, the prescribed medicine actually exacerbated the governance ailment that it was designed to cure. To illustrate, the rapid growth of executive compensation persisted and in some markets, accelerated after the introduction of individual executive pay disclosure. In the financial sector, the shift toward a board dominated by independent directors perceived by many to be key for effective monitoring of management ultimately proved to be its Achilles' heel as weak industry knowledge meant that non-executive directors were unable to pick up on warning signs of imprudent risk taking by management. This section will examine how the core set of corporate governance instruments comprising transparency, independent monitoring, economic incentives, shareholder rights, and financial liability has been applied to different issues and contexts. It will discuss the extent to which these mechanisms have been effective and analyze the limits of their application by surveying cases where they have failed to work as intended. In addition, it will set forth proposals to improve the use of specific tools and suggest how certain governance issues should be addressed.